Reduction of Environmental Pollution in Africa: ICT and Greenhouse Emissions (European journal of volunteering and community-based projects, 2024)
The level of carbon dioxide (CO2) emissions is under constant scrutiny by many scholars. This is due to the level of growth of the world population and of the Information and Communication Technologies (ICT) sector and consequently to the ever-increasing global economic development, which contribute significantly to the increase in energy consumption and the consequent increase in emissions of CO2. The aim of this study is to examine how CO2 emissions grow with population growth and whether this can be related to industrialization. To achieve this objective, an analysis was conducted on panel data based on Africa over a period of 42 years (1971-2012). The results of the study confirm the relationship between population growth and CO2 emissions, highlighting that pollution in developing countries will increase significantly over 50 years. The study offers theoretical and practical implications. It contributes to expand the scientific literature and debate on the environmental conditions of Africa and provides useful suggestions for policymakers to implement industrial, urban, and social policies to build a global sustainable development that includes the poorest countries.
Keywords: CO2 emissions; ICT; developing economies; population growth; pollution; environment